2009
DOI: 10.1016/j.nepr.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the teacher program to assist nurse managers to educate nursing staff in Ecuadorian hospitals

Abstract: Continuing education for hospital staff nurses is a concern worldwide. Current research shows that continuing education among nurses can positively affect patient outcomes (O'Brien, T., Freemantle, N., Oxman, A, et al., 2002. Interactive continuing education workshops or conferences can improve professional practice and patient outcomes. Journal of Evidence Based Nursing. 26 (5)). Seeing a need for improved patient outcomes among hospitals in Ecuador, we conducted a teaching the teacher program to assist nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In this relation, Palmer too, studied training the head nurses as directors for obtaining stable in-service education, and he counted them as more efficient teachers relative to others (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this relation, Palmer too, studied training the head nurses as directors for obtaining stable in-service education, and he counted them as more efficient teachers relative to others (4).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have confirmed the need for continuous courses on management training for head nurses to deal with the new challenges of the health system (3), and they have emphasized on training head nurses as leaders as part of in-service education (4).…”
Section: Introductionmentioning
confidence: 99%
“…20 We and others have described standard approaches to adolescent palliative care, including how to assess patient readiness for end-of-life discussions, reframe goals, and engage teens in advance care planning. 18,19,41,42,45 The core attributes of successful communication with adolescents include (1) a systematic approach, including consistent time points for conversation and allowance of patient and family processing time 65 ; (2) direct, compassionate, nonjudgmental, concrete, and developmentally appropriate language 66,67 ; and (3) engagement of family, friends, and others who provide the patient with social support. 19 In addition, clinicians and family members must recognize the patient’s own communication preferences.…”
Section: Skills and Words That May Helpmentioning
confidence: 99%
“…While some countries computerize nursing documentation in the clinical history (15) , in others like Bolivia, it is limited to sketching out scarce theoretical notions without any practical development. Various studies have demonstrated that nursing education not only improves patient care, but is a critical need for the profession (16) . In this sense, Bolivian nursing's concern with adhering to an international method is understandable, for which it is key to determine its expectations and the meaning attributed to the nursing care process (17) .…”
Section: Discussionmentioning
confidence: 99%